Dissociating Affect and Deliberation in Choice Processes, 2001 - Peters, Ellen ([Verlag nicht ermittelbar], 2010)
This study was conducted to examine hypotheses derived from an emotion-based model of stigma responses to radiation sources. A model of stigma susceptibility was proposed in which affective reactions and cognitive worldviews activate predispositions to appraise and experience events in systematic ways that result in the generation of negative emotion, risk perceptions, and stigma responses. For this study, a total of 198 respondents were asked about a series of 15 objects and activities: sun-tanning, radiation therapy for cancer control, microwave ovens, nuclear power plants, radiation from air travel, death of a favorite pet, medical x-rays, the upcoming spring break, natural background radiation, final exams for the term, radiation from nuclear weapons testing, radiation to prevent bacteria in food, a series of thefts or crimes in their neighborhoods, cosmic radiation, and radioactive waste from nuclear power plants. Providing ratings on 17 scales, respondents gave their feelings about each object or activity, offered their opinions on situations wherein the object or activity would or would not be of concern, the impact of the object or activity in their lives, and their adjustment to situations involving the object or activity. Queries also included how angry and afraid the object or activity made respondents, and how risky, disgraceful, moral, acceptable, and stigmatized they felt it was. Finally, participants provided self-report ratings of affective reactivity and worldviews.